Perancangan Sistem Informasi Pelayanan Surat Menyurat pada Kantor Desa Tanjungsari Kutowinangun Kebumen Berbasis Desktop - Didin Agus Priyadi; Endah Wiji Lestari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
In today's era of globalization, information technology is speeding up. The computer that is a device that was created to facilitate human work, while achieving good progress in the manufacture of hardware and software. Tanjungsari Village Office requires a system that supports and provides a satisfactory service for its citizens. That's why the author tries to make the final task about the system of correspondence services at the Village Office Tanjungsari which until now has not been computerized. At this time Tanjungsari Village Office is only a government agency engaged in the field of community services. The existing system at Tanjungsari Village Office is still done manually, starting from the recording of the existing population data in Tanjungsari Village, to the storage of other data related to the process of correspondence service up to the making of the report, making it possible at the time of the process of going wrong in the recording, the inaccuracy of reports made and delays in searching the necessary data. The design of this system is the best solution to solve the problems that exist in this government agency, and with a computerized system can be achieved an effective and efficient activities in supporting activities in this government agency. The computerized system is better than the manual correspondence system to run more effectively and efficiently and the system is now more conducive than the previous system. The research method used is the method of obeservation where in this method the authors make direct observations at the office of Tanjungsari Village, the second study method where the author in this method the author uses books or files and reports as a reference, the third method of interview where the method of this interview directly interviewed secretary Tanjungsari village. With the results of research services to the population is still not maximal because the system used is still using the manual system so that service to the population becomes less effective and efficient.